Peningkatan Kualitas Siswa dalam Menguasai Bahan Ajar Al-Qur'an Hadis Melalui Penambahan Materi Matrikulasi yang Efektif dan Inovatif - Herliza, Yeti (JOEAI (Journal of Education and Instruction), 2019)
The purpose of this study is to analyze how far the efforts to improve the quality of students in mastering Al-Qur'an Hadith teaching materials, analyzing the content of matriculation material class X Madrasah Aliyah level and analyzing effective and innovative methods in the delivery of matriculation material. The research method uses a mixed approach to the Exploratory Sequential Design. Data collection by interview and observation which then continued with survey instruments in the form of a questionnaire. The results of the study, an increase in the quality of students in understanding and applying subject matter both from the results of cognitive evaluation and its application include: students in sufficient time can read the Al-Qur'an for those who have not, the better and phase reading the Qur'an, easy to understand the hadiths in learning material. Conclusions, from the results of research that has been done, through the addition of effective and innovative matriculation learning can improve the quality of students in mastering Al-Qur'an Hadith learning materials. Keywords: Quality, Teaching Materials, Matriculation Materials